Evaluation of ultraviolet-C lamps sterilization in veterinary operating theatre - Dito Anggoro; Setyo Budhi; Agus Purnomo; Dorothea Vera Megarani (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2019)
Ultraviolet (UV) lamp is the simplest method for sterilizing operating theatre. This method is effective, easily operated, and does not require high cost. Furthermore, there were several studies of microorganism contamination in the air and surface at human operating theatre. However, studies in veterinary operating theatre related to the effectiveness of UV light on sterilization process is still limited, especially in Indonesia. Bacterial contamination samples were collected three times each in three different conditions: A) before surgery and without UV, B) before surgery but UV was already used, and C) after surgery and UV was already used. Samples were taken with settle plate and swab method for collecting the air and operating table contamination, respectively. One-way repeated measures ANOVA determined that there was statistically significant difference in the number of bacterial contaminations between three conditions (A, B, and C) in settle plate method (p=0.009), as well as in swab method (p=0.010). The result revealed that the UV light was effective to sterilize operating theatre, which can be seen from the significant decreases on the number of bacterial contaminations before and after the UV was used, both in settle plate and swab method. The result of this study supported the theory that the UV light can reduce the air bacterial and surface contamination at operating theatre. However, the result of microorganism contaminations in this study was still not appropriate based on the standard minimum of total bacterial in the operating theatre from The Ministry of Health, Republic of Indonesia. Consequently, the use of another method of sterilization at the operating theatre is still required for a better sterilization result.